Naxalbari and Jhapa Revolt: Historical Study - Pokhrel, Rajkumar (Tribhuvan University Journal, 2018)
Naxalbari is a small village in West Bengal, India, where a section of the Communist Party of India (CPM) led by Kanu Sanyal,and Jangal Santhal initiated a violent uprising in 1967. On 18 May 1967, the Siliguri Kishan Sabha, of which Jangal was the president, declared their support for the movement initiated by Kanu Sanyal and readiness to adopt armed struggle to redistribute land to the landless. But before it, as a consequence of the debate in international communist movement, Indian communist Party split and a faction choose the path of Mao Thought to go ahead. The party was led by Charu Majumdar, Kanu Sanyal and Jangal Santhal revolted against the existing political system. The uprising was started from Naxalbari village by using the policy of “annihilation of class enemy”. It is known as Naxalbari Revolt. But the neither could gain achievement nor run for long last. Top leader of the party, Charu Majumdar, was arrested and killed. After his murder, the party split into more than one dozen factions. On the other side, in Nepal, the neighboring district Jhapa came into influence of Naxalbari Revolt and the youth communists of Jhapa started the revolt using the same path of Naxalbari. Jhapa Revolt also runs for only 30 months. Both the movements became failure to achieve the aim. But due to the differences of ruling structure, existing political system, and geo political condition between two countries, the revolt of India split into several divisions and the movement of Nepal, even being unsuccessful to achieve the aim achieved to unify the divided movement. The impact of Naxalbari movement in India seems remain still now in some parts of India but in Nepal, Jhapa revolt has become a history. Whatsoever, both revolts have left impact in both countries till now.